Reflectance confocal microscopy - Consensus terminology glossary in Brazilian Portuguese for normal skin, melanocytic and non-melanocytic lesions - Juliana Casagrande Tavoloni Braga; Carlos B. Barcaui; Ana Maria Pinheiro; Ana Maria Fagundes Sortino; Cristina Martinez Zugaib Abdalla; Gabriella Campos-; Gisele Gargantini Rezze; Juan Pineiro-Maceira; Lilian Licarião Rocha; Marcus Maia; Bianca Costa Soares de Sá (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background: Currently, there is no uniform and official terminology in Portuguese for reflectance confocal microscopy analysis, despite the increasing number of Brazilian dermatologists using this new tool. Objective: To present the terminology in Brazilian Portuguese for the description of reflectance confocal microscopy and establish the first Brazilian consensus on terms related to normal skin and cutaneous tumors. Methods: 10 Brazilian specialists from different institutions and states of Brazil were selected to evaluate the best corresponding terms in Portuguese for normal skin, melanocytic and non-melanocytic tumors. The terms used were translated from international consensuses in the English language. The modified Delphi method was used to create the consensus in 3 steps. Results: The terms considered the most appropriate in the Portuguese language to describe the findings of normal skin, melanocytic and non-melanocytic lesions in the reflectance confocal microscopy analysis were presented. Study limitations: The limitations of the present study include the number of participants and limited regional representation (only two of the five Brazilian regions were represented). Conclusion: This Brazilian consensus represents an opportunity for dermatologists and physicians specializing in cutaneous oncology to become familiar with reflectance confocal microscopy, propagating the technique in clinical and research environments to stimulate national and international publications on this subject.